An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A.; Szymanska, Katarzyna; Nguyen, Thanh-Minh T.; Racher, Hilary; Phelps, Ian G.; Toedts, Grischa; Kennedy, Julie; Wunderlich, Kirsten A.; Sorusch, Nasrin; Abdelhamed, Zakia A.; et al. (Nature Cell Biology, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
EVALuna2:9277

DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Keßler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif Bülent; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific Reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
EVALuna2:9281

Functional analyses of Pericentrin and Syne-2 interaction in ciliogenesis - Falk, Nathalie; Keßler, Kristin; Schramm, Sinja-Fee; Boldt, Karsten; Becirovic, Elvir; Michalakis, Stylianos; Regus-Leidig, Hanna; Noegel, Angelika A.; Ueffing, Marius; Thiel, Christian; Roepman, Ronald; Brandstätter, Johann Helmut; et al. (Journal of Cell Science, 2018)
Pericentrin (Pcnt) is a multifunctional scaffold protein and mutations in the human PCNT gene are associated with several diseases, including ciliopathies. Pcnt plays a crucial role in ciliary development in olfactory receptor neurons, but its function in the photoreceptor-connecting cilium is unknown. We downregulated Pcnt in the retina ex vivo and in vivo via a virus-based RNA interference approach to study Pcnt function in photoreceptors. ShRNA-mediated knockdown of Pcnt impaired the development of the connecting cilium and the outer segment of photoreceptors, and caused a nuclear migration defect. In protein interaction screens, we found that the outer nuclear membrane protein Syne-2 (also known as Nesprin-2) is an interaction partner of Pcnt in photoreceptors. Syne-2 is important for positioning murine photoreceptor cell nuclei and for centrosomal migration during early ciliogenesis. CRISPR/Cas9-mediated knockout of Syne-2 in cell culture led to an overexpression and mislocalization of Pcnt and to ciliogenesis defects. Our findings suggest that the Pcnt-Syne-2 complex is important for ciliogenesis and outer segment formation during retinal development and plays a role in nuclear migration.
EVALuna2:34620

Identification of the deregulated NEK1 protein network in skeletal ciliopathies - Vogl, C.; Keßler, Kristin; Gießl, Andreas; Kirchner, P.; Büttner, Christian; Ekici, Arif Bülent; Reis, André; Thiel, C. T. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Lack of a Retinal Phenotype in a Syne-2/Nesprin-2 Knockout Mouse Model - Falk, Nathalie; Joachimsthaler, Anneka; Keßler, Kristin; Lux, Uwe; Noegel, Angelika Anna; Kremers, Jan; Brandstätter, Johann Helmut; Gießl, Andreas (Cells, 2019)
Syne-2 (also known as Nesprin-2) is a member of a family of proteins that are found primarily in the outer nuclear membrane, as well as other subcellular compartments. Syne-2 contains a C-terminal KASH transmembrane domain and is part of a protein network that associates the nuclear envelope to the cytoskeleton via the binding to actin filaments. Syne-2 plays a role in nuclear migration, nuclear positioning during retinal development, and in ciliogenesis. In a previous study, we showed a connection between Syne-2 and the multifunctional scaffold protein Pericentrin (Pcnt). The elimination of the interaction of Syne-2 and Pcnt showed defects in nuclear migration and the formation of outer segments during retinal development, as well as disturbances in centrosomal migration at the beginning of ciliogenesis in general. In this study, the Syne-2 KO mouse model Nesprin-2oABD (Syne-2(tm1Ngl), MGI) with special attention to Pcnt and ciliogenesis was analyzed. We show reduced expression of Syne-2 in the retina of the Syne-2 KO mouse but found no significant structural-and only a minor functional-phenotype. For the first time, detailed expression analyses showed an expression of a Syne-2 protein larger than 400 kDa (similar to 750 kDa) in the Syne-2/Nesprin-2 KO mouse. In conclusion, the lack of an overt phenotype in Syne-2/Nesprin-2 KO mice suggests the usage of alternative translational start sites, producing Syne-2 splice variants with an intact Pcnt interaction site. Nevertheless, deletion of the actin-binding site in the Syne-2/Nesprin-2 KO mouse revealed a high variability in scotopic oscillatory potentials assuming a novel function of Syne-2 in synchronizing inner retinal processes.
CRIS-Team WoS Importer:2019-11-29

MAP4-dependent regulation of microtubule formation affects centrosome, cilia, and golgi architecture as a central mechanism in growth regulation - Zahnleiter, Diana; Hauer, Nadine; Keßler, Kristin; Uebe, Steffen; Sugano, Yuya; Neuhauss, Stephan C. F.; Gießl, Andreas; Ekici, Arif Bülent; Blessing, Holger; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Human Mutation, 2015)
Numerous genes are involved in human growth regulation. Recently, autosomal-recessive inherited variants in centrosomal proteins have been identified in Seckel syndrome, primary microcephaly, or microcephalic osteodysplastic primary dwarfism. Common hallmarks of these syndromic forms are severe short stature and microcephaly. In a consanguineous family with two affected children with severe growth retardation and normocephaly, we used homozygosity mapping and next-generation sequencing to identify a homozygous MAP4 variant. MAP4 is a major protein for microtubule assembly during mitosis. High-expression levels in the somite boundaries of zebrafish suggested a role in growth and body segment patterning. The identified variant affects binding sites of kinases necessary for dynamic instability of microtubule formation. We found centrosome amplifications in mitotic fibroblast cells in vivo and in vitro. These numeric centrosomal aberrations were also present during interphase resulting in aberrant ciliogenesis. Furthermore, affected cells showed a dysfunction of the microtubule-dependent assembly of the Golgi apparatus, indicated by a significant lack of compactness of Golgi membranes. These observations demonstrated that MAP4 mutations contribute to the clinical spectrum of centrosomal defects and confirmed the complex role of a centrosomal protein in centrosomal, ciliary, and Golgi regulation associated with severe short stature.
EVALuna2:9244